2008
DOI: 10.1095/biolreprod.108.069591
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Urban Air Pollution Affects the Functional Morphology of Mouse Placenta1

Abstract: In humans, adverse pregnancy outcomes (low birth weight, prematurity, and intrauterine growth retardation) are associated with exposure to urban air pollution. Experimental data have also shown that such exposure elicits adverse reproductive outcomes. We hypothesized that the effects of urban air pollution on pregnancy outcomes could be related to changes in functional morphology of the placenta. To test this, future dams were exposed during pregestational and gestational periods to filtered or nonfiltered air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
118
1
27

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(149 citation statements)
references
References 59 publications
3
118
1
27
Order By: Relevance
“…Veras et al [33] showed that ambient levels of PM may impair reproductive health by affecting the maternal side of the placental interface between the mother and the fetus. Preand/or gestational exposure of female mice to non-filtered urban air led to reduced volumes, diameters, and surface areas of maternal blood spaces and significant increases in fetal capillary surface area and the total and mass-specific morphometric diffusive conductances for oxygen of the intervascular barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Veras et al [33] showed that ambient levels of PM may impair reproductive health by affecting the maternal side of the placental interface between the mother and the fetus. Preand/or gestational exposure of female mice to non-filtered urban air led to reduced volumes, diameters, and surface areas of maternal blood spaces and significant increases in fetal capillary surface area and the total and mass-specific morphometric diffusive conductances for oxygen of the intervascular barrier.…”
Section: Discussionmentioning
confidence: 99%
“…D'autres hypothèses, comme celle d'un effet des polluants atmosphériques sur la circulation foeto-placentaire sont explorées. Chez le rongeur, des travaux ont montré que l'exposition prénatale aux particules issues du trafic routier (les animaux étant exposés directement au trafic), affecte la fonction placentaire [51]. Chez l'homme, l'exposition aux particules PM 10 et au dioxyde d'azote a été associée à des variations du poids du placenta ou du ratio foeto-placentaire [52].…”
Section: La Pollution Atmosphériqueunclassified
“…The pregnancy period is critical because mother's exposure to air pollutants could affect the fetal development of humans and animals.Studies in animals and humans had demonstrated the association between the mother's exposure to air pollutants, neonatal mortality and birth defects [1][2][3][4]. Veras et al [3] demonstrated an increase in transplacental diffusion of substances in female mouse which were exposed to air pollution at ambient level during the pre-pregnancy and pregnancy periods.…”
mentioning
confidence: 99%
“…Veras et al [3] demonstrated an increase in transplacental diffusion of substances in female mouse which were exposed to air pollution at ambient level during the pre-pregnancy and pregnancy periods. In 2009 [4], the same researchers showed that females which inhaled PM (particulate matter) at ambient level presented a decrease in the number of cicles, of folicules and embryo implantation as well as lower weight of puppies.…”
mentioning
confidence: 99%